ZnO Nanoparticle Formation from the Molecular Precursor [MeZnOtBu](4) by Ozone Treatment in Ionic Liquids: in-situ Vibrational Spectroscopy in an Ultrahigh Vacuum Environment - Bauer, Tanja; Voggenreiter, Markus; Xu, Tao; Wähler, Tobias; Agel, Friederike; Pohako-Esko, Kaija; Schulz, Peter; Döpper, Tibor; Görling, Andreas; Polarz, Sebastian; Wasserscheid, Peter; Libuda, Jörg (Zeitschrift für Anorganische und Allgemeine Chemie, 2017)
As reported previously, novel ZnO nanostructures can be grown by oxidation of [MeZnOtBu](4) building blocks with O-3 in ionic liquids (ILs). In this study, we have explored the role of the IL during ZnO formation by in-situ infrared reflection absorption spectroscopy (IRAS) in ultrahigh vacuum (UHV). [MeZnOtBu](4) and [C(2)C(1)Im][OTf] were (co-)deposited as thin films by physical vapor deposition (PVD) onto Au(111), separately or simultaneously. The IR spectrum of [MeZnOtBu](4) was analyzed between 300 and 4000 cm(-1) based on calculated spectra from density-functional theory (DFT). Spectral changes in the IL-related bands during the thermal treatment of [MeZnOtBu](4) in [C(2)C(1)Im][OTf] indicate the loss of the precursor ligands and the interaction of the IL with the growing ZnO aggregates. The films were treated with ozone (10(-6) mbar) in UHV and the spectral changes were monitored in-situ by IRAS. Slow ozonolysis of [C(2)C(1)Im][OTf] is observed. Spectroscopically we identify the primary ozonide formed by addition of O-3 to [C(2)C(1)Im](+) and suggest a reaction mechanism, which leads to a biuret derivative. Upon ozone treatment of mixed [MeZnOtBu](4)/[C(2)C(1)Im][OTf] films, ZnO aggregates are formed at the IL/vacuum interface. Ozonolysis of [C(2)C(1)Im][OTf] is suppressed. Upon annealing to 320 K, further ZnO aggregates are formed, leading to enclosure of [C(2)C(1)Im][OTf] in the ZnO film. At 380 K the IL is released from the mixed film. The pure [C(2)C(1)Im][OTf] desorbs at 420 K, leaving behind the ZnO phase.
Keywords: Ionic liquid; Ozone; IR spectroscopy; ZnO nanoparticles; Surface science